KEFEKTIFAN PEMBERLAKUAN SURAT IJIN USAHA PERDAGANGAN (SIUP) DI DESA SAMBOGUNUNG KABUPATEN DUKUN – GRESIK (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
The small business sector plays a very important role. Therefore, in this globalization era, small businesses need licensing, especially in the field of trade, given that there are still many forms of business that do not have a Trading Business License (SIUP). By having a business permit, the business activities carried out are not preoccupied with issues of control or demolition. The benefits obtained from the ownership of the business permit are as a means of legal protection. The researcher looked for the influence of the relationship between the application of SIUP to the empowerment of small businesses. The results of the study show that the existence of SIUP greatly helped the existence of Pande Besi entrepreneurs in Sambogunung Village, Dukun - Gresik in empowering their businesses. This can be seen from the existence of legal protection from the local government towards their businesses, the ease of applying for capital loans thanks to the existence of SIUP, and easy to establish cooperative relations with other parties thanks to the existence of SIUP.